Low-Energy Fragmentation Dynamics at Copahue Volcano (Argentina) as Revealed by an Infrasonic Array and Ash Characteristics - Hantusch, Marcia; Lacanna, Giorgio; Ripepe, Maurizio; Montenegro, Veronica; Valderrama, Oscar; Farias, Camila; Caselli, Alberto; Gabellini, Pietro; Cioni, Raffaello (Frontiers in Earth Science, 2021)
Ash-rich eruptions represent a serious risk to the population living nearby as well as at thousands of kilometers from a volcano. Volcanic ash is the result of extensive magma fragmentation during an eruption, and it depends upon a combination of magma properties such as rheology, vesicularity and permeability, gas overpressure and the possible involvement of external fluids during magma ascent. The explosive process generates infrasonic waves which are directly linked to the outflow of the gas-particle mixture in the atmosphere. The higher the overpressure in the magma, the higher should be the exit velocity of the ejected material and the acoustic pressure related to this process. During violent eruptions, fragmentation becomes more efficient and is responsible for the extensive production of ash which is dispersed in the atmosphere. We show that the phase of intense ash emission that occurred during March 2016 at Copahue volcano (Argentina) generated a very low (0.1 Pa) infrasonic amplitude at 13 km, raising a number of questions concerning the links among acoustic pressure, gas overpressure and efficiency of magma fragmentation. Infrasound and direct observations of the eruptive plume indicate that the large quantity of ash erupted at Copahue was ejected with a low exit velocity. Thus, it is associated with eruptive dynamics driven by a low magma overpressure. This is more evident when infrasonic activity at Copahue is compared to the moderate explosive activity of Villarrica (Chile), recorded by the same array, at a distance of 193 km. Our data suggest a process of rigid fragmentation under a low magma overpressure which was nearly completely dissipated during the passage of the erupting mixture through the granular, ash-bearing crater infilling. We conclude that ash released into the atmosphere during low-energy fragmentation dynamics can be difficult to monitor, with direct consequences for the assessment of the related hazard and management of eruptive crises.